Whom to blame for Judah's doom? A narratological and intertextual Analysis of 2 Kgs 23:30-25:30 - Collinet, Benedikt J. (2023)
The Babylonian exile is considered one of the worst trauma experiences in the context of HB/OT, with which a multitude of biblical texts are concerned. The final chapters of 2 Kings offer various theological interpretations of how and why the exile had to occur. Narratively, the study approaches the pericope and seeks to identify these interpretive models.